Sustainable tourism practices among hotels in Malaysia: financial and non-financial benefits - Samdin, Zaiton; Mohammad Afandi, Syamsul Herman; Kasimu, A. B.; Hassan, Hamimah (Penerbit Universiti Malaysia Terengganu, 2016)
The Sustainable Tourism Practice (STP) is one of the more recent practices within the hotel sector. One of the major reasons for hotels’ involvement in Sustainable Tourism Practices is to achieve some form of benefit. This paper attempts to highlight the significant benefits of STP for the hotel industry in Malaysia. It is believed that studies related to the contributing role of STP to the hotel industry in a developing country like Malaysia are relatively scarce. Therefore, this paper intends to bridge this knowledge gap by uncovering the benefits (i.e. financial and non-financial) hotels stand to reap in adopting various programmes which safeguard the environment. The study utilized the survey questionnaire method involving 60 hotel organisations in Kuala Lumpur and the state of Selangor. The study findings indicate the benefits of improved public image and the provision of safe and healthy environments to the hotel guests as the major benefit of hotels adopting STP. Unlike previous studies which identified financial contributions to the STP among hotels in developed countries, it appears that Malaysian hotels project their image to the guests after which it is expected that they will attract large patronage leading to financial gains. In conclusion, the results of this study have the potential of contributing to the knowledge as well as the hotel organisations.